Syntheses, structures and luminescent properties of Zn/Cd coordination polymers based on 4′-(2-carboxyphenyl)-3, 2′:6′, 3″-terpyridine. (1st September 2018) - Wang, Ting-Ting; Zhang, Jun-Lin; Hu, Huai-Ming; Cheng, Yue; Xue, Li-Li; Wang, Xiaofang; Wang, Bo-Zhou
Graphical abstract: Six new Zn/Cd coordination polymers based on 4′-(2-carboxyphenyl)-3, 2′:6′, 3″-terpyridine ligand have been synthesized by hydrothermal conditions and shown diversified frameworks. The pH value plays a key role on the final structure via affecting the numbers of coordinated water molecules. The thermal stability and luminescent properties were also studied. Abstract: Six new Zn/Cd coordination polymers (CPs) based on a new terpyridine derivative ligand, namely, [ZnLCl] n · n H2 O (1 ), [ZnL2 ] n (2 ), [CdL2 (H2 O)2 ] n (3 ), [CdL2 (H2 O)] n (4 ), [Cd2 L2 ( m -bdc)(H2 O)2 ] n (5 ), [Cd2 L2 ( m -bdc)(H2 O)] n (6 ), (H2 ( m -bdc) = benzene-1, 3-dicarboxylic acid, HL = 4′-(2-carboxyphenyl)-3, 2′:6′, 3″-terpyridine), have been synthesized under hydrothermal conditions and characterized by elemental analyses, infrared spectra, single-crystal X-ray diffraction. Compound 1 displays a 3D utp topology based on left- and right-handed helical chains. Compounds 2, 3 and 4 are three kinds of 1D loop chain structures. Compound 5 features a (3, 6)-connected 3D topology with point symbol of {4 2 ·6}2 {4 4 ·6 2 ·8 8 ·10}. Compound 6 reveals a (3, 6, 8)-connected 3D framework with point symbol of {4·5 2 }2 {4 8 ·5 6 ·6 8 ·7 4 ·8·9}{4 8 ·6 6 ·7}. Luminescent properties of compounds 1 –6 at room temperature were investigated.